Evaluation of the antibody response against Hepatitis B Virus infection in patients on maintenance hemodialysis: A Pilot Study (Bangladesh Journal of Medical Science, 2009)
Objective: This study was undertaken to evaluate the antibody response of hepatitis B virus infection in patients on maintenance hemodialysis (MHD) by detecting different viral markers. Method: Study subjects comprised a total of 88 chronic kidney disease (CKD) patients from Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) and Bangabandhu Sheikh Mujib Medical University (BSMMU). Of them 63 patients on MHD and 25 predialysis patients served as cases and controls respectively. Clinical history was taken and serological markers for HBV (HBsAg, Anti-HBs, and Anti-HBc) were determined by using ELISA. Results: Hepatitis B virus was positive in 1.6% of maintenance hemodialysis (MHD) patients and in 16% of controls (p